Molecular characterization of amikacin, kanamycin and capreomycin resistance in M/XDR-TB strains isolated in Thailand - Angkanang Sowajassatakul; Therdsak Prammananan; Angkana Chaiprasert; Saranya Phunpruch (My University, 2014)
The emergence of multidrug-resistant tuberculosis (MDR-TB) and extensively drug-resistant tuberculosis (XDR-TB) makes the treatment and control of tuberculosis difficult. Rapid detection of drug-resistant strains is important for the successful treatment of drug-resistant tuberculosis; however, not all resistance mechanisms to the injectable second-line drugs such as amikacin (AK), kanamycin (KM), and capreomycin (CAP) are well understood. This study aims to validate the mechanisms associated with AK, KM, and CAP resistance in M. tuberculosis clinical strains isolated in Thailand. A total of 15,124 M. tuberculosis clinical strains were isolated from 23,693 smear-positive sputum samples sent from 288 hospitals in 46 of 77 provinces of Thailand. Phenotypic analysis identified 1,294 strains as MDR-TB and second-line drugs susceptibility was performed in all MDR-TB strains and revealed 58 XDR-TB strains. Twenty-nine KM-resistant strains (26 XDR-TB and 3 MDR-TB) could be retrieved and their genes associated with AK, KM, and CAP resistance were investigated compared with 27 KM-susceptible strains. Mutation of the rrs (A1401G) was found in 21 out of 29 KM-resistant strains whereas mutations of eis either at C-14 T or at G-37 T were found in 5 strains. Three remaining KM-resistant strains did not contain any known mutations. Capreomycin resistance was determined in 28 of 29 KM-resistant strains. Analysis of tlyA revealed that the A33G mutation was found in all CAP-resistant strains and also in susceptible strains. In contrast, the recently identified tlyA mutation T539G and the novel Ins49GC were found in two and one CAP-resistant strains, respectively. In addition, our finding demonstrated the insertion of cytosine at position 581 of the tap, a putative drug efflux encoding gene, in both KM-resistant and KM-susceptible strains. Our finding demonstrated that the majority of KM resistance mechanism in Thai M. tuberculosis clinical strains was rrs mutation at A1401G. Mutations of the eis promoter region either at C-14 T or G-37 T was found in 5 of 29 strains whereas three strains did not contain any known mutations. For CAP resistance, 3 of 28 CAP-resistant strains contained either T539G or Ins49GC mutations at tlyA that might be associated with the resistant phenotype.
Keywords: Capreomycin; Amikacin; Kanamycin; Extensively drug-resistant tuberculosis; Tuberculosis Research and Epidemiology